Does Video-Assisted Mediastinoscopy Offer Lower False-Negative Rates for Subcarinal Lymph Nodes Compared with Standard Cervical Mediastinoscopy? - Citak, Necati; Buyukkale, Songul; Kok, Abdulaziz; Celikten, Alper; Metin, Muzaffer; Sayar, Adnan; Gurses, Atilla (The Thoracic and Cardiovascular Surgeon, 2014)
Objectives Theoretically, video-assisted mediastinoscopy (VAM) offers improved staging of subcarinal lymph nodes (LNs) compared with standard cervical mediastinoscopy (SCM).Materials and Methods Between 2006 and 2011, 553 patients (SCM, n = 293; VAM, n = 260) with non–small cell lung carcinoma who underwent mediastinoscopy were investigated. Mediastinoscopy was performed only in select patients based on computed tomography (CT) or positron emission tomography CT scans in our center.Results The mean number of LNs and stations sampled per case was significantly higher with VAM (n = 7.65 ± 1.68 and n = 4.22 ± 0.83) than with SCM (n = 6.91 ± 1.65 and 3.92 ± 86.4; p < 0.001). The percentage of patients sampled in station 7 was significantly higher with VAM (98.8%) than with SCM (93.8%; p = 0.002). Mediastinal LN metastasis was observed in 114 patients by mediastinoscopy. The remaining 439 patients (203 patients in VAM and 236 in SCM) underwent thoracotomy and systematic mediastinal lymphadenectomy (SML). SML showed mediastinal nodal disease in 23 patients (false-negative [FN] rate, 5.2%). The FN rate was higher with SCM (n = 14, 5.9%) than with VAM (n = 9, 4.4%), although this difference was not statistically significant (p = 0.490). Station 7 was the most predominant station for FN results (n = 15). The FN rate of station 7 was found to be higher with SCM (n = 9, 3.8%) than with the VAM group (n = 6, 2.9%; p = 0.623).Conclusion FN were more common in mediastinoscopy of subcarinal LNs. VAM allows higher rates of sampling of mediastinal LN stations and station 7, although it did not improve staging of subcarinal LNs.
Keywords: lung cancer; mediastinal staging; mediastinoscopy